STUDY OF SAKA MONUMENTS IN THE LOWER SYRDARYA AND AMUDARYA BASINS (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article analyzes the results of the study of cultural monuments of the Saka tribes of the Early Iron Age located in the lower basinsof the Syr Darya and Amu Darya rivers. The research, based on archaeological excavations, findings, and written sources, examines thelifestyle, religious beliefs, craftsmanship, and burial rituals of the Saka tribes who lived in these regions. Particular attention is given tosignificant archaeological sites such as Tozabog‘yoq, Chirik-Rabat, Koktepa, and others, which provide insights into the socio-economiclife of Saka society. The article also briefly outlines the history of research on these monuments, highlighting the scientific studies carried out since the second half of the 20th century. This study contributes to uncovering important aspects of the ancient Saka civilization on the territory of present-day Uzbekistan.